Synthesis of 1-Phenyl Naphthalene and Pericarbonyl Lignans - Deo, Sujata; Inam, Farhin; Mahashabde, R.P.; Jadhav, A.N. (Asian Journal of Chemistry, 2010)
The approach towards synthesis of 1-phenyl naphthalene and pericarbonyl lactone by cyclization of Perkin condensation product, arylidene β-benzoyl propionic acid with polyphosphoric acid and concentrated sulphuric acid can be achieved in one step.